Computer Cognitive Rehabilitation in Older People: gradior Program - José Miguel TORIBIO-GUZMÁN; Esther PARRA VIDALES; M.ª José VIÑAS RODRÍGUEZ; Yolanda BUENO AGUADO; M.ª Teresa CID BARTOLOMÉ; Manuel A. FRANCO-MARTÍN (Aula, 2018)
In the process of aging, there is a cognitive decline due to age. Cognitive impairment is one of the most common symptoms of neurodegenerative diseases such as dementia. Throughout decades, different types of cognitive interventions and approaches have been developed with the main objective of improving or maintaining the cognitive capacities of the elderly. Such is the case of computer cognitive rehabilitation that has been shown to be an effective form of stimulation capable of improving cognitive functioning in the older people. This document describes the computerized cognitive rehabilitation program gradior 4.5 (latest version), specifying its different components, application methodology and its most relevant aspects. The experience developed during the more than 20 years of existence of the program with thousands of patients coming from different devices and the different studies of efficacy and usability developed, in order to satisfy the needs, capacities, limitations and preferences of the users, have given place to this new improved version that makes it a flexible, dynamic, simple, useful and easy to use tool.